A roadmap to recovery: ABCD recommendations on risk stratification of adult patients with diabetes in the post COVID-19 era - Choudhary, P; Wilmot, EG; Owen, K; Patel, DC; Mills, L; Rayman, G; Winocour, P; Ayman, G; Patel, R; Hambling, C; Nagi, DK (Wiley, 2020)
A third of the over 40,000 deaths in the UK attributed to the first wave of the COVID‐19 pandemic occurred in people with diabetes. However, the focus on emergency response to COVID‐19 in the first few months has had a major knock‐on impact on the delivery of routine clinical care for diabetes. Key challenges as we enter the second wave of the pandemic include a backlog of appointments, delays in accessing care such as structured education, and initiating insulin, GLP‐1 or diabetes technology. We anticipate ongoing pressures through increased commitments to general medicine, reductions in clinic capacities due to social distancing and reorganisation of clinic spaces. Many services have already adapted by moving much of their activity to the virtual space.